Creating a Competency Domain Index: Enhancing assessment for online programming and electronic design for lower secondary school - Tang, Jing Rui; Wan Ahmad, Wan Nurlisa; Mohd Zaihidee, Fardila; Jian Hong Me (Environment-Behaviour Proceedings Journal, 2025)
This study develops a Competency Domain Index (CDI) to enhance the assessment of online programming and electronic design for lower secondary schools in Malaysia. Conducted in two phases, the first identifies relevant competencies using the Nominal Group Technique (NGT), while the second develops the CDI with expert reviews. Results show over 70% expert consensus across all domains. The proposed CDI employs a spider web chart to visualise competencies, which are categorised according to Bloom’s taxonomy of cognitive levels, using normalised scores. Future work will focus on validating the CDI in schools to ensure its effectiveness and applicability.